ANALISIS PENGARUH STRUKTUR KEPEMILIKAN, KOMISARIS INDEPENDEN, KARAKTERISTIK PERUSAHAAN DAN RASIO KEUANGAN TERHADAP KONDISI FINANCIAL DISTRESS PADA PERUSAHAAN PUBLIK - Syahril Ramadhan (Jurnal Akuntansi Bisnis, 2017)
This research seeks to examine whether independent board and ownership structure are associated with the probability of experiencing financial distress in listed companies. Companies are categorized as having financial distress if their yearly net profit during 2005-2007 is negative. Ownership variables used are ownership by institutional investor, insider (board of directors or commissioners) and blockholders. Logit model is used to test the research problem on 69 financially distress companies’ data and their 69 paired data samples. Using firm size (ln asset), leverage , liquidity and profitability ratio as control variables, this research finds that financial distress is significantly affected by institutional investor, insider (board of directors or commissioners) and blockholders, firm size (ln asset), leverage , liquidity and profitability ratio. Key Words : Struktur Kepemilikan, Komisaris Independent, Karateristik Perusahaan, Rasio Keuangan, Financial Distress